Validation of the portuguese version of the international physical activity questionnaire for adolescents (IPAQA) - Ferro-Lebres, Vera (2018)
Questionnaires have been broadly used to assess physical activity in adolescents, however validation studies, although essential, are not always performed. Objective: The present work aims to determine the validity of the Portuguese version of the International Physical Activity Questionnaire for Adolescents against 3 axis Actigraph accelerometers. Method: A cross-sectional study was conducted, with a sample of 222 adolescents, with a mean age of 15.6 years (SD=2.05). After translation and cross cultural adaptation, data obtained from the questionnaire was correlated to accelerometers data, using Spearman correlation coefficient. Percentages of agreement of physical activity tertiles obtained by each method were tested using Cohen’s Kappa. Statistical analysis was performed for the total sample, per sex and per age group. Results: A significant correlation between the questionnaire and accelerometer was found for older adolescent boys, for total physical activity (ρ=0.372; P<0.01), and for moderate to vigorous physical activity (ρ=0.428; P<0.01) No correlations were found for the younger adolescents and girls. A 42.3% agreement was found for the questionnaire and accelerometer tertiles of total physical activity. Conclusion: The concurrent validity proved that the questionnaire might be valid only for older adolescent boys. The authors consider that whenever available physical activity objective measurements should be used instead of questionnaires.